Color atlas of pathology : pathologic principles, associated diseases, sequela - Riede, Ursus-Nikolaus , 1941-; Werner, Martin , 1887-1964 (Thieme, 2004)
"Ideal for students, and helpful for residents, this compact book presents - in beautiful full color - the full range of pathological findings in the human body. Beginning with the fundamentals, a team of expert pathologists guides the reader systematically through all classes and types of disease using: more than 1,100 outstanding photographs, micrographs, and electron microscopic images; schematic drawings that illustrate processes, such as the course of an infection; text boxes with clinical and morphological information; and clever learning tools and mnemonic devices."--BOOK JACKET